2019
DOI: 10.1039/c9sm01288e
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of active polar emulsions: from linear to unidirectional and inviscid flow, and intermittent viscosity

Abstract: The rheological behaviour of an emulsion made of an active polar component and an isotropic passive fluid is studied by lattice Boltzmann methods. Different flow regimes are found by varying the values of shear rate and extensile activity (occurring, e.g., in microtubule-motor suspensions). By increasing activity, a first transition occurs from linear flow regime to spontaneous persistent unidirectional macro-scale flow, followed by another transition either to (low shear) intermittent flow regime with coexist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 67 publications
(98 reference statements)
1
31
0
Order By: Relevance
“…Finally, we found that the effective viscosity of the system increases together with the intensity of the contractile activity. Such dynamic behavior is drastically different from that of the extensile mixture under shear, which is found to exhibit a multi-stable dynamics characterized by states at null and negative viscosity 36 , in agreement with the experimental results of Lopez and Guo.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…Finally, we found that the effective viscosity of the system increases together with the intensity of the contractile activity. Such dynamic behavior is drastically different from that of the extensile mixture under shear, which is found to exhibit a multi-stable dynamics characterized by states at null and negative viscosity 36 , in agreement with the experimental results of Lopez and Guo.…”
Section: Introductionsupporting
confidence: 88%
“…The equilibrium properties of the system are encoded in a modified Landau–Brazovskii 34 36 , 39 , 40 free-energy functional that can be expressed as the first contribution defines the thermodynamic property of the binary mixture: The first term allows for the segregation of the two phases when , as the free energy has two minima at and , respectively corresponding to the passive and active phase, while . The gradient terms determine the surface tension.…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A suspension of cytoskeletal filaments and motor proteins is a paradigmatic example of active matter. [1][2][3][4] This system is active as the filaments can be moved with respect to each other by molecular motors, which consume chemical energy in the form of ATP and drive the system out of equilibrium. A typical example of such motors is given by kinesin 5 and its synthetic analogues that were shown to cross-link microtubules (MTs) and to push them apart.…”
Section: Introductionmentioning
confidence: 99%